2009
DOI: 10.1364/josaa.26.000847
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between threshold and suprathreshold perception of position and stereoscopic depth

Abstract: We seek to determine the relationship between threshold and suprathreshold perception for position offset and stereoscopic depth perception under conditions that elevate their respective thresholds. Two threshold-elevating conditions were used: (1) increasing the interline gap and (2) dioptric blur. Although increasing the interline gap increases position (Vernier) offset and stereoscopic disparity thresholds substantially, the perception of suprathreshold position offset and stereoscopic depth remains unchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…This interpretation is supported by manual depth made matches by observers who viewed large-disparity clinical stereotargets while one eye was blurred. 1,3 A similar underestimation of perceived suprathreshold depth for line stereotargets that were identical to those in the current study was reported for conditions of binocular image blur by Patel et al 4 The depth matches of the three observers from Patel et al, 4 who viewed line stereotargets with +2.00 D lenses in front of both eyes, are compared to the results for the monocular-blur condition in the current study in Figure 2A.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This interpretation is supported by manual depth made matches by observers who viewed large-disparity clinical stereotargets while one eye was blurred. 1,3 A similar underestimation of perceived suprathreshold depth for line stereotargets that were identical to those in the current study was reported for conditions of binocular image blur by Patel et al 4 The depth matches of the three observers from Patel et al, 4 who viewed line stereotargets with +2.00 D lenses in front of both eyes, are compared to the results for the monocular-blur condition in the current study in Figure 2A.…”
Section: Discussionsupporting
confidence: 85%
“…Patel et al 4 demonstrated that increasing the separation between the two lines of the stereotarget also elevates the stereothreshold (see also 5,6 ). However, unlike the introduction of binocular image blur, an increase in the line separation results in no reduction of perceived suprathreshold depth.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Note that although the resulting dynamic range compression of perceived depth under scotopic conditions clearly is a suprathreshold effect, the luminance contrast-dependent ratio s() of perceivable disparity thresholds in photopic and scotopic conditions is used for this manipulation. Patel et al [2009] observe that in the presence of blur not only the stereoscopic disparity thresholds are increased, but also the perceived suprathreshold stereoscopic depth is reduced. They attempt to explain their data on the perceived depth reduction using various sensory-perception transducer functions, including the logarithmic compression employed in our work, in which case the gain factor must be reduced.…”
Section: Disparity Processingmentioning
confidence: 85%